Crime and punishment in Islamic law theory and practice from the Sixteenth to the Twenty-First century - Peters, Rudolph (Cambridge University Press, 2005)
This is the first single-authored account of both the theory and practice of Islamic criminal law. It will be invaluable for students, and scholars in the field, as well as for professionals looking for a comprehensive coverage of the topic.